2013
DOI: 10.1186/1471-2105-14-121
|View full text |Cite
|
Sign up to set email alerts
|

BioCode: Two biologically compatible Algorithms for embedding data in non-coding and coding regions of DNA

Abstract: BackgroundIn recent times, the application of deoxyribonucleic acid (DNA) has diversified with the emergence of fields such as DNA computing and DNA data embedding. DNA data embedding, also known as DNA watermarking or DNA steganography, aims to develop robust algorithms for encoding non-genetic information in DNA. Inherently DNA is a digital medium whereby the nucleotide bases act as digital symbols, a fact which underpins all bioinformatics techniques, and which also makes trivial information encoding using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…The coding DNA of a gene is transcribed by codons of three nucleotide bases that specify amino acids to encode proteins. The watermark should be embedded into coding DNA by considering codon degeneracy, to preserve the protein sequence, and codon optimization, including codon usage and GC content [10,11]. Codon degeneracy and optimization make it difficult to embed a large number of bits into coding DNA.…”
Section: Requirements Of Reversible Data Hiding In Dna Sequencementioning
confidence: 99%
See 3 more Smart Citations
“…The coding DNA of a gene is transcribed by codons of three nucleotide bases that specify amino acids to encode proteins. The watermark should be embedded into coding DNA by considering codon degeneracy, to preserve the protein sequence, and codon optimization, including codon usage and GC content [10,11]. Codon degeneracy and optimization make it difficult to embed a large number of bits into coding DNA.…”
Section: Requirements Of Reversible Data Hiding In Dna Sequencementioning
confidence: 99%
“…Recently, it has been shown that the genome of a genetically tractable organism can be used as a medium for data hiding depending on the required application [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The coding DNA of a gene is transcribed by codons of three nucleotide bases that specify amino acids to encode proteins.…”
Section: Requirements Of Reversible Data Hiding In Dna Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…The potential of DNA has been realized for various information-theoretic protocols, including DNA steganography for the identification of genetically modified organisms [12,21,23] hiding of messages in DNA [9,11,16,20] and long-term data storage in DNA [3,7,8,10,14,21]. These applications require mechanisms to validate, ensure, and possibly verify message accuracy.…”
Section: Introductionmentioning
confidence: 99%